Stories From Under The Sky - Madson, John (Book collections on Project MUSE., 1998)
In Stories from under the Sky, John Madson salutes the outdoor life. These thirty-six essays display his healthy respect for the forces of nature, without diminishing his wry awareness of the foibles of beast, bird, fish, and human. In sections on mammals, the river, and birds, Madson acquaints readers with some real characters-not all of them four-footed! Some are old favorites: the raccoon, the otter, the fawn, and the badger. Others are less familiar-the demonic shrew, the indomitable dogfish, and the exotic blue heron. Even the "unloved" come in for their share o.